Exploring the emotional experiences of young women with chronic pain: The potential role of self-compassion. (March 2021) - Barnes, Alexandra; Adam, Margo EK; Eke, Abimbola O; Ferguson, Leah J
Chronic pain is multidimensional and includes an emotional dimension in addition to the physical and cognitive dimensions. Self-compassion, being touched by and open to one's own suffering, has been identified as a useful resource during difficult experiences. The purpose of this narrative inquiry was to explore the role of self-compassion in the emotional experiences of women with chronic pain. Seven women participated in focus groups, reflective photo voice and one-on-one interviews. Three collective narratives were generated highlighting the women's sources of emotional pain and suggesting self-compassion as a constructive approach to manage the emotional dimension of chronic pain.